(untitled) (PANGEEA, 2025)
This article analyzes the activities conducted with institutionalized adults with disabilities in a residential care and assistance center. The sample consists of 50 adults with intellectual disabilities receiving multidisciplinary services, including social work, psychological services, habilitation and rehabilitation, care and assistance, activities for independent living and social integration. Data were collected through document analysis and observation of beneficiary files over a six-month period. The results describe activity patterns across six areas and highlight variations according to disability severity and social contact status, including cases with and without family contact. The study discusses implications for rehabilitation practice and the role of staff training in delivering tailored activities to enhance autonomy and well-being.